A systematic model for improving theoretical garment fit. Issue 4 (4th July 2018) - Hernández, Niina; Mattila, Heikki; Berglin, Lena
Abstract : Purpose: The purpose of this paper is to use a systematic model for detecting misfit between the garment and the target group. Design/methodology/approach: Using an empirical–analytical methodology, the systematic model was tested. The input data were run through the model to generate the output data, which were analysed, including basic statistics. The purpose of the analysis was to detect misfit and improve the garment measurement chart. This procedure was repeated until a clear result was reached. Findings: The result of this study is an optimised garment measurement chart, which considers the garment's ease, different sizes/proportions in relation to a target group. The results show that it is possible to use a systematic model to define the shortcomings of a garment´s range of sizes and proportions. Research limitations/implications: Further studies are needed to verify the results of the theoretical garment fit and their values in relation to real garment fit. Practical implications: If the systematic model is implemented to improve the theoretical garment fit, this may have effects on the available garment sizes and its proportions, resulting in increased theoretical garment fit for the target group. Originality/value: The paper presents a systematic model for detecting and eliminating theoretical fitting; the model includes both garment ease allowance and defined points of misfit.